Stopping Spam - Goodman, Joshua; Heckerman, David; Rounthwaite, Robert (Scientific American, 2005)
In 1978 the first spam e-mail—a plug from a marketing representative at Digital Equipment Corporation for the new Decsystem-20 computer—was dispatched to about 400 people on the Arpanet. Today junk correspondence in the form of unwanted commercial solicitations constitutes more than two thirds of all e-mail transmitted over the Internet, accounting for billions of messages every day.